A comprehensive review of dynamic voltage restorers. (November 2017) - Farhadi-Kangarlu, Mohammad; Babaei, Ebrahim; Blaabjerg, Frede
Highlights: A comprehensive review on dynamic voltage restorers is presented. Power circuit topologies as well as the control methods used for DVR have been presented in details. Topologies and control methods of DVR have been classified and possible advantages and disadvantages are discussed. Specific application of DVRs are also considered. Abstract: During the last half century the Power Quality (PQ) related problems have become important issues. Many solutions have been proposed to address the PQ problems. The most attractive and flexible way is to use power electronic converter based devices such as Dynamic Voltage Restorer (DVR), Distribution Static Compensator (DSTATCOM), Unified Power Quality Conditioner (UPQC), Uninterruptible Power Supply (UPS), and other devices usually called custom power devices. Among custom power devices, the DVR is the most economical solution to overcome the voltage-related PQ problems. Intensive research has been done in the field of DVR and the field is rather mature now. But, a survey on the published papers showed that there is not any published paper that reviews the DVR technology. This paper tends to provide a comprehensive review on the DVR topologies, control strategies and applications. We will consider all of the fast voltage compensators, i.e. the devices called Static Series Compensator (SSC), sag corrector, Dynamic Sag Corrector (DySC), and other similar devices are also considered. All of these devices will be called DVR since they operate almost in the same way. Some comparative conclusions are also provided. This paper can be beneficial for the researchers and engineers, who want to do investigations on DVRs.